Symposium 4: Learning about new tools: A Case study of Digilab and Digiquests - Mills, Keren; Scantlebury, Non; Parker, Jo (Proceedings of the International Conference on Networked Learning, 2010)
This paper examines an innovative approach prototyped to deliver staff development at The Open University (OU). The Digilab creative space was built within The Open University Library for staff to engage “hands on” with technologies which have the potential to enhance learning, both for experimentation and for familiarisation. Initially users were encouraged to explore the technologies at their own pace in the Digilab, but a survey of OU staff carried out in 2007 indicated that whilst in the main staff embraced the idea of working with new technologies, many lacked the confidence to tackle using them without support. As such, structured experiential activities to support staff in developing their skills have been developed. ‘Digiquests’ are supported by a mixed team of elearning professionals from academic and academic related backgrounds. These quests require staff to navigate their way through technology themed topics using a variety of accessible devices and immersive environments to support reflective learning, the main objective being maximising hands-on experimentation. The resulting activities form a suite of self paced and collaborative opportunities to encounter some of the key issues, constraints and possibilities for developing technology enhanced experiential learning for learners and practitioners within a safe, informal and neutral space. Shorter, self-paced ‘digibytes’ have also been developed. Participation in Digilab activities is steadily increasing, and in addition to the original aim, of developing the skills of academic staff, a number of additional uses of the space have been realised. Feedback has been positive, indicating that participants appreciate the nature of the space, the opportunity to interact with the technologies provided there, and recognise that the experiences help support new ways of thinking about technology. The Digilab team will continue to work closely with other units to integrate our hands-on activities into the university’s staff development offerings. The Digilab is also increasingly being used by course teams and developers to test course materials on different platforms, such as mobile phones and game consoles, or to explore the integration of technology enhanced learning into course models.